An Anatomical Study of Phana Marma w.s.r to Dushta Pratishyaya (Chronic Rhinosinusitis) - Vikas Mishra; S. S Gupta (AYUSHDHARA, 2025)
Marmas are essential places throughout the body. The term Marma originates from the Sanskrit root "Mru" and refers to a critical area or point in the body, where injury can lead to severe repercussions. It also signifies the essential life essence. According to Acharya Sushruta, Ayurveda elucidates approximately 107 Marmas, specifically in Jathruurdva. Marmas are regarded as significant sites of Prana, and Phanamarma, classified under Vaikalya-Karamarma, is situated on either side of the nostrils, which serve as the conduit for Phana marma, emanating from the Ghrana sangyavaha srotas. Olfactory loss can be partial (hyposmia) or total (anosmia), and may be transient or enduring, contingent upon the underlying reason. The term Phana refers to the enlarged lateral aspect of the nose or the inflated hood of a serpent. The site of Phana Marma presents a divergence of view between Acharya Sushruta and Vagbhata (Astanga Sangraha); yet, both elucidate the analogous Viddha lakshana. Therefore, this study is conducted to resolve the ambiguity of its placement. Chronic rhinosinusitis is a common illness with significant physical and social consequences in daily life. Accessible diagnostic tools must be both cost-effective and reasonably predictive for all persons. X-ray PNS radiography employing the Water’s view may aid in the diagnosis of sinusitis. This study aimed to evaluate the predictive effectiveness of X-ray PNS 450 (Water’s view) in the initial diagnosis of chronic rhinosinusitis.